Deep intronic variant in MVK as a cause for mevalonic aciduria initially presenting as non‐syndromic retinitis pigmentosa. Issue 6 (14th August 2022) - Dvaladze, Anna; Tavares, Erika; Di Scipio, Matteo; Nimmo, Graeme; Grudzinska‐Pechhacker, Monika K.; Paton, Tara; Tumber, Anupreet; Li, Shuning; Eileen, Christabel; Ertl‐Wagner, Birgit; Mamak, Eva; Hoffmann, Georg; et al.
Abstract: Non‐syndromic retinitis pigmentosa (NSRP) is a clinically and genetically heterogeneous group of disorders characterized by progressive degeneration of the rod and cone photoreceptors, often leading to blindness. The evolving association of syndromic genes to cause NSRP and the increasing role of intronic variants in explaining missing heritability in genetic disorders present challenges in establishing conclusive clinical and genetic diagnoses. This study sought to identify and validate the causative genetic variant(s) in a 13‐year‐old male initially diagnosed with NSRP. Genome sequencing identified a pathogenic missense variant in MVK [NM_000431.3:c.803T>C (p.Ile268Thr)], in trans with a novel intronic variant predicted to create a new donor splice site (c.768+71C>A). Proband cDNA analysis confirmed the inclusion of the first 68 base pairs of intron 8 that resulted in a frameshift in MVK (r.768_769ins[768+1_768+68]) and significantly reduced the expression of reference transcript (17.6%). Patient re‐phenotyping revealed ataxia, cerebellar atrophy, elevated urinary mevalonate and LTE4, in keeping with mild mevalonic aciduria and associated syndromic retinitis pigmentosa. Leakage of reference transcript likely explains the milder phenotype observed in our patient. This is the first association of a deep intronic splice variant to cause MVK ‐related disorder. This report highlights the importance of variant validation and patient re‐phenotyping in establishing accurate diagnosis in the era of genome sequencing. Abstract : We report a case with an intronic variant in MVK (c.768+71C>A) in trans with a known pathogenic variant (p.Ile268Thr) that presented as non‐syndromic retinitis pigmentosa. Proband re‐phenotyping revealed cerebellar atrophy, a common feature of mevalonic aciduria. Biochemically, proband's urine mevalonate levels were similar to what is described in Hyper IgD syndrome.